Analisis Pembelian Bahan Baku Menggunakan Metode Economic Order Quantity (EOQ) di PT. Wirataco Mitra Mulia - Efra Diana; Rita Hartati (Universitas Teuku Umar, 2022)
Purchasing raw materials aims to obtain an item that is needed by the company so that we carry out transactions to get the goods needed to achieve a smooth production process at the company. In purchasing raw materials, companies usually have a capacity in purchasing to save costs in order to provide benefits for the company. PT Wirataco Mitra Mulia is a company that processes in the field of stockpiling and asphalting of the Trumon Singkil boundary road. The results of research at PT Wirataco Mitra Mulia use of raw materials every day as much as 300m3/day, while it the purchasing section the average is 600m3/day. As a result of purchasing too many raw materials, it causes purchasing costs to increase in the company and experience wasted costs in purchasing raw materials. The purpose of this study is to analyze the purcashe of raw materials that are the most economical, efficient, and at a lower cost by using the Ecenomic Order Quantity (EOQ) method. From the results of the calculation of the Ecenomic Order Quantity (EOQ) method, the total cost of purchasing raw materials (sirtu) is Rp 131.400.000, 657 treps, safety stock is 5400m3, reorder point is 27.200m3.